THE EFFECTIVENESS OF USING E-JOBSHEET IN TEACHING MACHINE CONTROL SYSTEM PRACTICE - Erwin Komara Mindarta; Windra Irdianto; Fuad Indra Kusuma; Andika Bagus Nur Rahma Putra; M. Ihwanudin (Universitas Brawijaya, 2018)
Jobsheet as a tool in practice that functioned as a tool for school and utilized by the learners. While e-jobsheet is the guidance for practice electronically. This study was conducted to help improve vocation student performance, especially fixing systems on the machine by Engine Control Module (ECM). Using the e-jobsheet as a Learning Source for 21st Century Students, hoping that students will be easier to understand the substance and learning outcomes so e-jobsheet is effectively implemented. This study used pre-experimental design with one pretest-postest group. The population is all diploma 3rd students in the automotive machine of vocational education of Malang State University. Sampling is done by purposive sampling technique in student of 4th semester. The data retrieval technique in this research is done through the tests. Data analysis techniques in this study using the test